Perbandingan Algoritma Sorting dengan Menggunakan Bahasa Pemograman Javascript dalam Penggunaan Waktu Komputasi dan Penggunaan Memori - Wijaya, Surya; Fauziah, Fauziah; Harjanti, Trinugi Wira (Universitas Indraprasta PGRI Jakarta, 2024)
Data that is sequential or neatly arranged data is highly necessary because sorted data makes it easier to read, inspect, and correct any erroneous data. In information technology, there are many algorithms for data sorting, including merge sort, insertion sort, heap sort, quick sort, selection sort, shell sort, and so on. In this test, seven sorting algorithms (Merge Sort, Insertion Sort, Bubble Sort, Heap Sort, Quick Sort, Selection Sort, and Shell Sort) were used with random data testing scenarios of 100, 150, and 200 data points, using the JavaScript programming language. The research findings indicate that insertion sort is the most efficient algorithm in terms of time, with an average time of 0.613 seconds. Quick sort is the most efficient algorithm in terms of memory, with an average memory usage of 31072 Kb.